Interactive Media: The Semiotics of Embodied Interaction - O’Neill, Shaleph (Springer, 2017)
Interactive media is pervasive. The colonization of our everyday lives by the computational power of the silicon chip is a fundamental feature of our digital age, and raises important questions such as: What does this mean for us as inhabitants of such media rich environments? How can we make sense of these media and the ways in which they have changed our interactions? What theories can we draw on to help us make sense of life in the digital age? Human Computer Interaction has been looking at versions of these questions for a long time now, but as technology advances so quickly it is hard to keep pace with the changes. In reflecting on some of these issues and by providing a way to relate some of the disparate threads of theory from fields such as phenomenology, cognitive science, semiotics and the ecological theory of perception, Shaleph O’Neill provides an exploration of the theories that impact our understanding over a spectrum of interactive media. Dr. Shaleph O’Neill is Course Director of Interactive Media Design at the University of Dundee.